Analisis Sejarah Kepemimpinan setelah Wafatnya Nabi Muhammad SAW - Subhani Subhani; Salamatun Raudhah; Sufian Hadi; Mustafa Mustafa; Maritsa Ulfa Khaira (Departement of Mathematics Education, 2023)
The history of the caliphate after the death of the Prophet Muhammad from time to time has the same pattern starting from the phases of development, formation, coaching, glory, decline and destruction. This study aims to determine the history of the Khulafaur Rashidun dynasty after the death of the Prophet Muhammad SAW. This study used qualitative research methods. The data collection technique was carried out by means of a literature study through exploration of journals and other information relevant to the study. The results of the study show that the leadership after the death of the Prophet Muhammad was continued by the Khulafur Rasyidin Caliphate, the Umayyad Dynasty, the Abbasid Dynasty, the Fatamiyah Dynasty and the Seljuq Dynasty.